Economic valuation and its determinates of improved irrigation water use; evidence based on South Gondar Zone, Ethiopia - Aklok Getnet; Ermias Tesfaye; Yasin Ahmed; Mohammed Ahmed (Cogent Economics & Finance, 2022)
The main aim of the research was to analyze economic evaluation and determinants of willingness to pay decisions for efficient irrigation water use improvement. Use for this purpose total of 300 HHs was selected using the Multi-stage sampling technique. The collected data was analyzed using econometrics model. In the econometric part, a seemingly unrelated bivariate probit model was applied to estimate households' mean willingness to pay and its determinant's for efficient irrigation water use. Leads by a double bounded dichotomous choice method. From seemingly unrelated bivariate probit model regression results, the mean and aggregate willingness to pay off the households 950.7 ETB ( exteuro25.7) per month per household per hectare was 1087159.09 ETB ( exteuro29382.7) per month and (12*1087159.09 = 13045909.08 ETB per year) respectively. The Mean and aggregate willingness to pay from the open-ended questions to be 926.059 ETB ( exteuro25.03) per month per household per hectare was 1072990.52 ETB ( exteuro28,999.74) per month respectively also, The bivariate probit model result revealed that bid values, sex of the household head, irrigation farm size, extension service significantly affected households' WTP in both initial and followed up bid values So, policymakers should be households have a high willingness to pay for improved irrigation water use systems and the government should implement irrigation water management practices to supply reliable irrigation water to the farmers and should set up proper irrigation water pricing at an amount close to the mean WTP that households were willing and able to pay.
Keywords: 330; willingness to pay; double bounded dichotomous choice; open ended question